2015
DOI: 10.1097/wad.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Public’s Knowledge and Understanding of Alzheimer’s Disease and Dementia

Abstract: This paper reports findings from a systematic review of the literature on the general public's knowledge and understanding of dementia/Alzheimer's disease. The key purpose of the review was to evaluate existing literature with specific attention paid to conceptual and methodological issues and to key findings. Over a 20-year period, 40 published articles satisfied the inclusion criteria. Only 4 of these were qualitative and 5 were cross-national. The review revealed a lack of consistency across studies regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
229
6
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(256 citation statements)
references
References 47 publications
15
229
6
6
Order By: Relevance
“…We selected as potential time-varying confounding variables: age, equivalized income (27), medical treatment for stroke, hypertension, diabetes (28), dyslipidemia (29), current smoking (30), current alcohol drinking (31), and daily walking time (32). Other time invariant characteristics, such as sex and educational attainment, were omitted from our fixed-effects regressions (33).…”
Section: Methodsmentioning
confidence: 99%
“…We selected as potential time-varying confounding variables: age, equivalized income (27), medical treatment for stroke, hypertension, diabetes (28), dyslipidemia (29), current smoking (30), current alcohol drinking (31), and daily walking time (32). Other time invariant characteristics, such as sex and educational attainment, were omitted from our fixed-effects regressions (33).…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, studies have reported large variations in dementia literacy even in high-income countries (710). In six European countries, the Facing Dementia Survey found that community residents had very limited knowledge of early signs and treatments of Alzheimer’s disease: more than 80% thought most people would not recognize early signs, and 76% thought there were no effective treatments (9).…”
Section: Introductionmentioning
confidence: 99%
“…Research into attitudes toward dementia often tends to focus on specific issues such as screening for dementia (Bond et al, 2010), euthanasia (Williams et al, 2007) or artificial feeding (Bryon, de Casterlé & Gastmans, 2008), rather than on wider issues. Moreover, these surveys often do not use validated scales (Cahill et al, 2015), or directly compare attitudes across settings, populations, or over time.…”
Section: Introductionmentioning
confidence: 99%